Design of Hybrid Dynamic Balancer and Vibration Absorber - Y. R. Wang; C. Y. Lo (Shock and Vibration)
This study proposed a novel hybrid dynamic balancer and vibration absorber that is cheaper than active dampers and more effective than passive dampers. The proposed damping system does not need to be altered structurally to deal with different damping targets. Rather, the proposed vibration absorber is capable of self-adjustment to the optimal damping location in order to achieve balance and, thereby, optimize damping effects. The proposed device includes a groove under the damping target with inertial mass hung from a coil spring beneath. This allows the device to bounce vertically or rotate in order to reduce vibrations in the main body. The coil spring vibration absorber can also slide along the groove in order to adjust its location continuously until the vibrations in the system are minimized and the main body is balanced. Experiments verify the efficacy of the proposed device in improving damping performance beyond what has been achieved using conventional devices. We also provide an explanation of the theoretical underpinnings of the design as well as the implications of these findings with regard to future developments.